(untitled) (Journal of Universal Science Research, 2025)
This paper explores the field of pragmatics and its relationship with other major branches of linguistics. Pragmatics, as a subfield of linguistics, focuses on the study of language in use and how context influences meaning. The paper discusses how pragmatics interacts with syntax, semantics, sociolinguistics, discourse analysis, and psycholinguistics. It highlights the importance of understanding the role of context, speaker intentions, and cultural norms in communication. The interdisciplinary nature of pragmatics is examined, showing its relevance to various linguistic theories and its practical applications in communication studies.